Uji Sterilitas Instrumen Bedah Selama Penyimpanan di Kamar Operasi IGD RSUD Dr. Moewardi - Kurniawan, Rizki Banjar; Hudiyono, .; Purwoko, . (Nexus Biomedika, 2013)
Background: Surgical Site Infection (SSI) in RSUD Dr. Moewardi still occurs frequently. SSI strongly relates to the sterilization quality of surgical instrument which is determined by the stage of sterilization process that includes cleaning, packaging, ordering in sterilizer, sterilizing process, distribution, and storage. The maximum storage length of sterile surgical instrument in IGD operating chamber of RSUD Dr. Moewardi is seven days. This research aimed to know the sterilization rate of surgical instrument stored in IGD operating chamber of RSUD Dr. Moewardi. Methods: Five samples were taken from post-steriliziation surgical instrument swab with varied storage length, those were 1 day, 2 days, 3 days, 4 days, 5 days, 6 days, and 7 days. A total of 35 samples were collected based on the rule of thumb with simple random sampling technique. Data were analyzed using Chi Square test. Results: The result of 5 samples of surgical instrument swab after 1 day Â storage was 1 positive sample with contamination and 4 negative samples. From 5 samples of surgical instrument swab after 2 and 3 days storage, there was not any positively contaminated samples. Five samples of surgical instrument swab after 4 and 5 days storage showed 4 samples positively contaminated and 1 sample negative. From 5 samples of surgical instrument swab after 6 and 7 days storage, there were 3 samples positively contaminated and 2 samples negative. The microorganisms of contaminant found were gram positive bacteria. The statistical analysis showed a significant relationship between the length of surgical instrument storage and the contamination of microorganism (p = 0.017). Conclusions: There was a significant difference of bacteria growth rate on surgical instruments based on storage length. Surgical instruments stored in IGD operating chamber of RSUD Dr. Moewardi > 3 days were 33 times more likely contaminated than the surgical instruments stored â¤ 3 days (OR = 32,67; p < 0,001). Keywords: sterility, contamination of surgical instrument, storage length.